Cholesterol efflux by acute-phase high density lipoprotein: role of lecithin:cholesterol acyltransferase1 - Weerapan Khovidhunkit; Judy K. Shigenaga; Arthur H. Moser; Kenneth R. Feingold; Carl Grunfeld (Journal of Lipid Research, 2001)
HDL plays an initial role in reverse cholesterol transport by mediating cholesterol removal from cells. During infection and inflammation, several changes in HDL composition occur that may affect the function of HDL; therefore, we determined the ability of acute-phase HDL to promote cholesterol removal from cells. Acute-phase HDL was isolated from plasma of Syrian hamsters injected with lipopolysaccharide. Cholesterol removal from J 774 murine macrophages by acute-phase HDL was less efficient than that by control HDL because of both a decrease in cholesterol efflux and an increase in cholesterol influx. LCAT activity of acute-phase HDL was significantly lower than that of control HDL. When LCAT activity of control HDL was inactivated, cholesterol efflux decreased and cholesterol influx increased to the level observed in acute-phase HDL. Inactivation of LCAT had little effect on acute-phase HDL. In GM 3468A human fibroblasts, the ability of acute-phase HDL to remove cholesterol from cells was also lower than that of normal HDL. The impaired cholesterol removal, however, was primarily a result of an increase in cholesterol influx without changes in cholesterol efflux. When control HDL in which LCAT had been inactivated was incubated with fibroblasts, cholesterol influx increased to a level comparable to that of acute-phase HDL, without any change in cholesterol efflux. These results suggest that the ability of acute-phase HDL to mediate cholesterol removal was impaired compared with that of control HDL and the lower LCAT activity in acute-phase HDL may be responsible for this impairment. The decreased ability of acute-phase HDL to remove cholesterol from cells may be one of the mechanisms that account for the well-known relationship between infection/inflammation and atherosclerosis.—Khovidhunkit, W., J. K. Shigenaga, A. H. Moser, K. R. Feingold, and C. Grunfeld. Cholesterol efflux by acute-phase high density lipoprotein: role of lecithin:cholesterol acyltransferase.